2014
DOI: 10.1021/ac403937e
|View full text |Cite
|
Sign up to set email alerts
|

Method for Characterization of Low Molecular Weight Organic Acids in Atmospheric Aerosols Using Ion Chromatography Mass Spectrometry

Abstract: The structural composition of PM2.5 monitored in the atmosphere is usually divided by the analysis of organic carbon, black (also called elemental) carbon, and inorganic salts. The characterization of the chemical composition of aerosols represents a significant challenge to analysts, and studies are frequently limited to determination of aerosol bulk properties. To better understand the potential health effects and combined interactions of components in aerosols, a variety of measurement techniques for indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…Organic acids were sensitive to (−)ESIMS. Most of these could easily lose neutral fragments such as 44 (CO 2 ), 28 (CO) and 18 (H 2 O) in MS 2 (Brent, Reiner, Dickerson, & Sander, ). In the positive ion mode, peptide signals were typically more abundant, and the fragment ions were more likely to delineate a large portion of the peptide sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Organic acids were sensitive to (−)ESIMS. Most of these could easily lose neutral fragments such as 44 (CO 2 ), 28 (CO) and 18 (H 2 O) in MS 2 (Brent, Reiner, Dickerson, & Sander, ). In the positive ion mode, peptide signals were typically more abundant, and the fragment ions were more likely to delineate a large portion of the peptide sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The certificate of analysis for SRM1649b used in this study has been reported previously. The water-soluble contents are primarily composed of low-molecular-weight ions (Ni, Cu, Cr, Mn, V, Fe, Al, Ca, Na, K, Mg, Pb, Cl − , F − , SO 4 2− , and NO3 − ) [ 43 ]. The organic extractable fraction contains polycyclic aromatic hydrocarbons, steranes, and hopanes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-nitrogenous low molecular weight organic acids (LMWOAs) are widely distributed in the natural environment, including water [22], soil [23] and atmosphere [24], and are also the end products of oxidation of many organic pollutants in drinking water treatment plants (DWTPs) [25,26]. Also, many non-nitrogenous LMWOAs, containing one or more carboxyl groups, are characterized by low molecular weight and hydrophilic behavior, and therefore likely to be poorly removed by conventional DWTPs using coagulation-sedimentation-filtration [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%